La projecció sintaxi-fonologia en els clítics del català i de l’espanyol - Harris, James (Caplletra. Revista Internacional de Filologia, 1995)
This article covers Spanish and Catalan clitic pronouns according to the fundamental theoretical principles of Distributed Morphology. The author postulates that the syntax-phonology mapping of clitics consists of two submappings, the first from syntax to morphology and the second from morphology to phonology. In this second mapping, the clitics may suffer the effect of various morphological rules, specifically, the structural operations of Impoverishment, Adjunction, Fusion and Fission. The author proves that the complex and quirky behaviour of clitics and clitic clusters in Spanish and Barceloní can be easily explained by taking into account that these four operations act on the clitics’ syntactical terminals in a morphological component which is intermediate between phonology and syntax.